Preservice educators' interpretations and pedagogical benefits of a STEM integration through agriculture, food and natural resources rubric - Hui-Hui Wang; Neil A. Knobloch (Journal of Pedagogical Research, 2022)
In the K-12 settings, teachers are encouraged to teach STEM subjects using a more integrated approach, and not be treated as stand-alone disciplines. STEM integration represents a way to think about curriculum change. It is a concept of how to restructure what is taught and what students learn. The nature of STEM disciplines no doubt creates certain challenges for STEM teachers. Despite researchers having made extensive progress in understanding of STEM integrative approaches, there are considerable barriers that relate to revolution of curriculum, assessment, and teaching practices in the K-12 STEM education system. For example, tools for assessing integrated STEM instruction have been developed, yet there has been limited implementation or adoption of teacher assessment for integrated STEM instruction. The purpose of this action research study was to understand how the preservice educators interpreted the language in the integrated STEM through AFNR rubric that was developed in 2018 (Wang & Knobloch, 2018). Four themes emerged when examining how preservice educators interpreted and applied the rubric for integrated STEM education: (1) Prejudgments based on prior knowledge and experiences, or course expectations informed interpretation of levels of STEM integration; (2) limited to no teaching experience resulted in novice interpretation of the integrated STEM lessons; (3) level one (Exploring) was a clean cut, but gray areas existed in interpreting levels two (Developing) and three (Advancing); and, (4) the rubric was a tool that helped preservice educators reflect on the purpose of teaching certain content/concepts. Preservice educators also gave recommendations to improve the rubric. Additionally, they recommended more scaffolding, examples, expert modeling, group discussion, and experiences when learning to use the rubric.